THE LEGAL CONSEQUENCES TOWARD THE DIFFERENCES OF MINUTES OF DEED AND DEED COPIES ISSUED BY THE NOTARY (VERDICT STUDY NUMBER 1/ PDT.G/2020/PN.SNT) - Ana Romasi Sigiro (NOMOI Law Review, 2022)
The Republic of Indonesia as a legal state based on Pancasila and the 1945 Constitution of the Republic of Indonesia guarantees certainty, order, and legal protection which are based on truth and justice; to ensure certainty, order, and legal protection. So that it takes written evidence that is authentic about the circumstances, events, or legal actions held through a certain position. As a public official who is authorized to make an authentic deed, a notary must be able to provide legal certainty to the society that uses the services of a notary. The authority of a notary according to Law number 2 of 2014 about the position of a notary Article 15 paragraph1 is to make an authentic deed regarding all acts, agreements and provision required by laws and regulations and desired by the interested parties, to be stated in an authentic deed, guaranteeing the certainty of the deed making date, keeping deeds, providing Grosse, deed copies and quotations, all as long as the making of the deed is not assigned or excluded to officials or other people stipulated by law. Not only authority that must be considered by the notary in carrying out his duties and positions, but there is one of the obligations of the notary as state in article 16 paragraph 1 letter d of the Notary Position Act that the notary is obliged to issue Grosse Deed, Deed copies or quotation based on minutes of deed.Keywords: Notary, Minutes of deed, Deed copies.